Mutations in TUBB8 cause a multiplicity of phenotypes in human oocytes and early embryos - Feng, Ruizhi (J Med Genet, 2016)
BACKGROUND: TUBB8 is a primate-specific β-tubulin isotype whose expression is confined to oocytes and the early embryo. We previously found that mutations in TUBB8 caused oocyte maturation arrest. The objective was to describe newly discovered mutations in TUBB8 and to characterize the accompanying spectrum of phenotypes and modes of inheritance. METHODS AND RESULTS: Patients with oocyte maturation arrest were sequenced with respect to TUBB8. We investigated the effects of identified mutations in vitro, in cultured cells, and in mouse oocytes. Seven heterozygous missense and two homozygous mutations were identified. These mutations cause a range of folding defects in vitro, different degrees of microtubule disruption upon expression in cultured cells, and interfere to varying extents in the proper assembly of the meiotic spindle in mouse oocytes. Several of the newly discovered TUBB8 mutations result in phenotypic variability. For example, oocytes harboring any of three missense mutations (I210V, T238M and N348S) could extrude the first polar body. Moreover, they could be fertilized, although the ensuing embryos became developmentally arrested. Surprisingly, oocytes from patients harboring homozygous TUBB8 mutations that in either case preclude the expression of a functional TUBB8 polypeptide nonetheless contained identifiable spindles. CONCLUSIONS: Our data substantially expand the range of dysfunctional oocyte phenotypes incurred by mutation in TUBB8, underscore the independent nature of human oocyte meiosis and differentiation, extend the class of genetic diseases known as the tubulinopathies, and provide new criteria for the qualitative evaluation of MII oocytes for IVF.